MANAGING MULTIPLE CHALLENGING ROLES: FAMILY, WORK AND PROFESSIONAL DEVELOPMENT - Natalia COJOCARU; Viorica ŞAITAN; Tatiana HODONOAGA (Moldova State University, 2018)
In the modern society, as researchers remarked, it is common to work and study at the same time, thus, academic and work domains are interdependent and influence each other continuously, frequently provoking inter-role conflict situations. In some cases, the conflict of the role can acquire a three-dimensional nature when work, family, and education come at play concomitantly. The strain may arise in this case from the difficulty to juggle these three roles and manage time properly while trying to pursue studies successfully, accomplish professional tasks in an efficient manner and fulfil responsibilities related to parenthood, marriage or private life. In this paper, we have proposed a case study of such triple role conflict (work-family-education) in the local academic context. We have conducted 14 in-depth interviews with junior members of academic staff that experience this three-dimensional conflict (PhD students with teaching duties, married, having small children). Our interest was to identify their perceptions concerning these conflictual experiences, the level of one or another role commitment, and their evaluations with reference to severity of conflict and its consequences on the academic results and efficiency, as well as the strategies used in order to manage this conflict. GESTIONAREA PROVOCĂRILOR MULTIPLE DE ROL: FAMILIE, MUNCĂ ȘI DEZVOLTARE PROFESIONALĂ În societatea modernă, relevă cercetătorii, este un fapt obișnuit să lucrezi și, în același timp, să urmezi un program de studii. Astfel, domeniul muncii și cel academic sunt interdependente și interferează continuu, creând, deseori, situații de conflict de rol. În anumite cazuri, acest conflict poate avea chiar o triplă solicitare concurențială de rol, care vine dinspre domeniile muncă, familie și studii. Conflictul, în acest caz, poate să apară ca urmare a dificultății de a gestiona timpul și eforturile necesare pentru a continua cu succes programul de studii, a realiza eficient sarcinile profesionale și a-și îndeplini responsabilitățile aferente rolului de părinte, soț/soție. În această lucrare, propunem un studiu de caz din mediul universitar autohton privind manifestarea acestui triplu conflict de rol (muncă-familie-studii). În acest scop, au fost intervievați 14 asistenți universitari care se confruntă cu asemenea situații de triplu conflict (doctoranzi, având și sarcini didactice, căsătoriți, cu copii mici). Interesul nostru a fost de a identifica percepțiile lor cu referire la aceste experiențe conflictuale, nivelul angajamentului față de un rol sau altul și evaluările pe care le fac cu privire la severitatea conflictului și consecințele acestuia asupra rezultatelor și eficienței academice, implicit strategiile pe care le utilizează în vederea gestionării solicitărilor de rol.